Early-Onset Marfan Syndrome: A Case Series - Ardhanari, Mohanageetha; Barbouth, Deborah; Swaminathan, Sethuraman (Journal of Pediatric Genetics, 2019)
Mutations in fibrillin 1 cause Marfan syndrome (MFS), an autosomal dominant disorder of the connective tissue, with multisystem manifestations. In early-onset MFS, the physical characteristics are expressed much earlier than the classical MFS. Those affected by this form generally have their mutations restricted to the gene “hotspot” region of exons 24 to 32. Historically, affected individuals usually die within the first few years of life due to heart failure secondary to severe valvular insufficiency. We report three patients with early-onset MFS, whose clinical evolution has been remarkably positive, when compared with other reported cases in the literature.
Keywords: Marfan syndrome; mitral valve prolapse; aortic root dilatation; FBN1 gene